Applications of Plasma‐Activated Water in Dentistry: A Review - Milhan, Noala Vicensoto Moreira [UNESP]; Chiappim, William; Sampaio, Aline da Graça [UNESP]; da Cruz Vegian, Mariana Raquel [UNESP]; Pessoa, Rodrigo Sávio; Koga‐ito, Cristiane Yumi [UNESP] (MDPI, 2022)
The activation of water by non‐thermal plasma creates a liquid with active constituents referred to as plasma‐activated water (PAW). Due to its active constituents, PAW may play an important role in different fields, such as agriculture, the food industry and healthcare. Plasma liquid technology has received attention in recent years due to its versatility and good potential, mainly focused on different health care purposes. This interest has extended to dentistry, since the use of a plasma–liquid technology could bring clinical advantages, compared to direct application of non‐thermal atmospheric pressure plasmas (NTAPPs). The aim of this paper is to discuss the applicability of PAW in different areas of dentistry, according to the published literature about NTAPPs and plasma–liquid technology. The direct and indirect application of NTAPPs are presented in the introduction. Posteriorly, the main reactors for generating PAW and its active constituents with a role in biomedical applications are specified, followed by a section that discusses, in detail, the use of PAW as a tool for different oral diseases.
Keywords: atmospheric plasma; DBD; decontamination; dentistry; gliding arc discharge; oral cancer; plasma‐activated water; plasma‐treated water; tooth bleaching